Macroeconomic Impacts of Immigration in the Canadian Atlantic Region: An Empirical Analysis Using the Focus Model - Peter Dungan; Tony Fang; Morley Gunderson; Steve Murphy (Institute of Labor Economics (IZA), 2023)
We simulate the impact of an increase in immigration into the Atlantic provinces based on the FOCUS macro-econometric model at the University of Toronto. That national model was adapted to reflect the regional dimensions of the Atlantic provinces. We find robust evidence of positive outcomes for the Atlantic region so long as it is part of a broader increase in immigration for the country as a whole. The positive outcome encompasses higher GDP and GDP per capita, higher consumption, and improved government fiscal balances at both the federal and provincial levels that could in turn be used for tax reductions or the enhancement of government services. These benefits could be enhanced further by carefully targeting new immigrants for needed skills and for their likelihood of remaining in the Atlantic region.
Keywords: J11; J15; J18; J24; 330; immigration; macroeconomic impacts; Atlantic Canada; FOCUS Model